EXPLORATION OF FACTORS INFLUENCING PATIENT DECISIONS IN CHOOSING A BEAUTY CLINIC: A GROUNDED THEORY APPROACH - Uliyah, Dian Alfiyatul; Dwi Cahyono; Haris Hermawan (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to explore the factors that influence patient decisions in choosing a beauty clinic. Method: The method used in this study was an in-depth interview with ten informants who were active patients of Dr. Dian’s Beauty Clinic in Jember. The data obtained were analyzed using the Grounded Theory approach. Results: The results showed that patient decisions were influenced by various factors, including clinic reputation, service quality, and previous experience. In addition, psychological aspects such as increased self-confidence and social recognition also play an important role in patient motivation to choose beauty services. Novelty: This study provides new insights into the complexity of consumer decision making in the context of modern aesthetic services, and emphasizes the importance of integration between service quality and marketing strategies that are responsive to patient needs. These findings are expected to provide practical contributions for beauty clinic managers in increasing competitiveness and customer loyalty.